2015
DOI: 10.1002/mgg3.132
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel mutations in Mexican patients with Aarskog–Scott syndrome

Abstract: Aarskog–Scott syndrome (AAS), also known as faciogenital dysplasia (FGD, OMIM # 305400), is an X-linked disorder of recessive inheritance, characterized by short stature and facial, skeletal, and urogenital abnormalities. AAS is caused by mutations in the FGD1 gene (Xp11.22), with over 56 different mutations identified to date. We present the clinical and molecular analysis of four unrelated families of Mexican origin with an AAS phenotype, in whom FGD1 sequencing was performed. This analysis identified two st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
(54 reference statements)
0
15
0
Order By: Relevance
“…In the following years, several other authors reported similar cases, describing patients whose phenotypes were characterised by the presence of variously associated signs, such as clinodactyly, brachydactyly, long philtrum, widow's peak, camptodactyly, interdigital webbing, and inguinal/umbilical hernia. ese supported the identification of a nosologically distinct condition [3,4]. In addition, various degrees of neurocognitive disabilities and/or behavior disorders were reported, ranging from attention deficit and hyperactivity disorder (ADHD) to severe intellectual disability.…”
Section: Introductionmentioning
confidence: 84%
“…In the following years, several other authors reported similar cases, describing patients whose phenotypes were characterised by the presence of variously associated signs, such as clinodactyly, brachydactyly, long philtrum, widow's peak, camptodactyly, interdigital webbing, and inguinal/umbilical hernia. ese supported the identification of a nosologically distinct condition [3,4]. In addition, various degrees of neurocognitive disabilities and/or behavior disorders were reported, ranging from attention deficit and hyperactivity disorder (ADHD) to severe intellectual disability.…”
Section: Introductionmentioning
confidence: 84%
“…Furthermore, to the best of our knowledge, no case of a Chinese patient with ASS has been previously reported. Table I presents the clinical manifestations of ASS in patients carrying the FGD1 mutation in different exons/introns, using information from previous studies ( 1 , 4 , 6 , 11 , 12 ). This may facilitate the direct analysis of genotype-phenotype correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are cases of clinically-evident AAS which could not be attributed to mutations in FGD1 . As a matter of fact, some researchers argue that the majority of AAS cases are still to be characterized molecularly, with FGD1 mutations being established in a mere 20% of the cases [6]. Consequently, cases are increasingly being subjected to molecular analysis in order to determine the underlying causative variant.…”
Section: Discussionmentioning
confidence: 99%